(untitled) (Collection of scientific works «Modern structures of metal and wood», 2025)
This work recognizes areas of rational use and the level of appropriate load increase for using external CFRP reinforcement to increase the stability of centrally compressed metal elements. An analysis of possible effective solutions for external CFRP reinforcement of compressed metal struts is presented and the principles of applied determination of general parameters of their stability are formulated. With symmetrical external reinforcement of compressed metal struts by FRP, their overall flexibility is reduced, which is ensured by the work of external reinforcement in the cross-sectional area that receives tension in the process of losing stability. Accordingly, the principles of practical determination of the overall stability of the considered structures are presented, taking into account the specific features of the combined operation of steel and FRP: significant heteromodulus of materials, additional temperature stresses that add to the load on the metal elements, the practical ability of FRP to effectively perceive only tensile forces, which changes the working position of the center of gravity of the cross-section upon loss of stability, as well as the inability of FRP systems that involve adhesive fastening, to be fully operational as part of a whole structure. Currently, there is a need for appropriate systematization and adaptation of existing global practices for reinforcing the elements in question with fiber plastics and for developing corresponding domestic standards. There is a need for appropriate development of applied methods for determining the overall stability of specified elements, based on the existing national regulatory framework for the calculation of metal structures and substantiated by the necessary experimental studies.